(3TQM bUjOI GdbUU GdMb aj eOM NjQ GdNdbs - (3Gdabjg eMeO Hf CHi HcQ GdebQis; (3jMji Hf TQa GdOjf Hf TeS GdOjf Hf GdegOj dOjf Gddg CMeO Hf jMji Hf GdeQJVjs ((3eOQSI UfYGA s)
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdbOhS GdOjGf , GdcQje GdMdje GdefGf , GdPi Ted HGddWa hGdEMSGf s
(3BNQgG (B:s
(3aGFMkG fTQgG ai cd fGO , fGejI HQcGJgG Edi jhe GdJfGO JeJ hHGdNjQ YeJ gPg GdbUjOI GdaQjOI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3cJHJ HCeQ GdbGVi Ydi Hf YHO Gddg Hf Ydi HQhGYs
(3hcJHJ CHjGJ GdbUjOI HNW eLhOs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs